Sosialisasi Adat Budaya Desa Kamarora B Kecamatan Nokilalaki Kabupaten Sigi - Daniel T. Todapa; Juemi Juemi (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2022)
The community service activity entitled "Socialization of Village Cultural Traditions" was carried out in Kamarora B Village, District. Nokilalaki Sigi Regency The aim of this community service activity is to empower and improve the quality of the existence of traditional villages in the context of preserving culture and strengthening character as national identity. Selection in Kamarora B Village Because Kamarora B Village is a village that has customs and culture which have begun to be eroded by the rapid flow of globalization, efforts are needed to preserve cultural customs as a filter and foundation for development in Kamarora B Village, Kec. Nokilalaki, Sigi Regency. This community service activity is carried out by conducting outreach which aims to increase the understanding and knowledge of Village Government Apparatus, Youth and the community regarding how important it is to maintain the cultural traditions of Kamarora B Village which have begun to be eroded by the times.